Internalisasi Nilai-nilai Agama dalam Membentuk Karakter Religius Siswa - Dahlan, Mukhtar Zaini (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research was conducted at the preschool level. The purpose of this study is to explain how the process of internalizing religious values occurs in the formation of religious character in children. This research was conducted at the Teratai 23 PAUD Post, Wonorejo Village, Kec. Kencong Kab. Jember This research uses purposive sampling in determining the research theme. The object of this research is the formation of religious character in childhood through the internalization of religious values. To obtain the data needed for this study, researchers used various data collection methods, including observation, interviews, and documentation, The data analysis used is ethnographic analysis. Due to the descriptive nature of the research, in this method, data consistent with factual findings at the site of the investigation are presented, analyzed, and conclusions are drawn. The values contained in the religious character are explained. Religious activities include daily prayers, reading and memorizing Asmaul Husna, reading short letters, taking a dhuha bath, and praying. In addition to implementing activities, Islamic-based character-framing methods are in the form of Parenting (Hadanah), Exemplary, Exercises and Dangers, Exemplary Stories, Dialogue, Practical Activities, and a supportive environment.